2019
DOI: 10.3389/fneur.2019.01084
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intestinal Microbiota and Probiotics Treatment in Children With Autism Spectrum Disorders in China

Abstract: Background: Most previous studies have found that human intestinal microbiota affect the symptoms of autism spectrum disorder (ASD), especially gastrointestinal (GI) symptoms, but regarding this, there is limited data of non-western ethnicity. Probiotics can reconstitute the host intestinal microbiota and strengthen gastrointestinal function, however, clinical data proving the effect of probiotics treatment on ASD is lacking.Methods: This study explored the significant differences between ASD and neurotypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 29 publications
4
77
0
5
Order By: Relevance
“…For example, the numbers of specific gut bacteria, which were predominantly from the family Lachnospiraceae and the genus Bacteroides , decreased in ASD children. These results were consistent with previous studies that reported the abundances of this family and genus were decreased in Chinese ASD children ( 24 , 25 ). However, a previous study, involving a Spanish cohort, showed that the abundance of Bacteroides increased in ASD children, which is inconsistent with our finding ( 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…For example, the numbers of specific gut bacteria, which were predominantly from the family Lachnospiraceae and the genus Bacteroides , decreased in ASD children. These results were consistent with previous studies that reported the abundances of this family and genus were decreased in Chinese ASD children ( 24 , 25 ). However, a previous study, involving a Spanish cohort, showed that the abundance of Bacteroides increased in ASD children, which is inconsistent with our finding ( 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…Porphyromonadaceae, Prevotellaceae, Bacteroidales, and Lachnospiraceae were more abundant in the ASD animal model ( 40 ). An increasing number of studies showed that gut microbiota disturbances were associated with ASD patients, and modulation of the gut microbiota improved symptoms in ASD patients ( 7 , 64 , 65 ).…”
Section: The Neuroprotective Role Of a Kd In The Central Nervous Systemmentioning
confidence: 99%
“…The improvement lasted up to 9 months after discontinuation of treatment. Niu et al [148] applied a combination of applied behavior analysis (ABA) training and probiotic administration for 4 weeks in children with ASD. Although it was difficult to distinguish from the effects of ABA, the results showed that the symptoms of ASD patients taking probiotics, as measured by the Autism Treatment Evaluation Checklist, improved.…”
Section: Therapeutic Approaches Via the Gut Microbiota For Asdmentioning
confidence: 99%